Penetapan Sanksi Pidana Dan Tindakan Sebagai Sistem Pemidanaan Di Indonesia - Rabith Madah Khulaili Harsya; Abdul Fatakh; Umdah Aulia Rohmah (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2022)
Abstract— The purpose of the dam punishment is how criminal sanctions and actions act as a criminal system that applies in Indonesia where the pattern of punishment as a reference can be immediately followed up by the established assessment system because of the guidelines made by the legislators so as not to cause confusion or overlap between the forms of sanctions from the type of criminal sanctions to the form of action, the sanctions for actions that are applied in actions considering the forms of additional sanctions are more open and more oriented to the basic ideas of criminal sanctions. The dual track system must be the basis for the policy of determining sanctions in laws and regulations, this system allows the utilization of types of criminal sanctions and proportional actions for comprehensive countermeasures. The basic idea of ??the expected double track system is that criminal sanctions and actions must be accommodated in every existing statutory regulation.